STUDIES ON SEASONAL VARIATION OF INDOOR AIRBORNE FUNGAL SPORES IN RABBIT HOUSE - R.PAVAN; S.U. PONNAMMA; K. MANJUNATH (International Journal of Pharma and Bio Sciences, 2014)
The indoor airborne fungal spore survey has been conducted for one year to assess the seasonal variation of the fungal flora in a rabbit house situated at Hessaraghatta village, near Bangalore city. The investigation was carried out by using an Andersen two stage viable sampler, at monthly intervals over a period of 12 months from January 2011 to December 2011. A total of 1.16 x 104 CFU/m3 belonging to fifteen different genera, excluding some unidentified ones were recorded. The differences in distribution among these fungi for seasonal and meteorological factors were correlated and the mean significant difference was expressed statistically at 0.05% and 0.01% level of significance.